A Ã¢â‚¬Å“RESENDSÃ¢â‚¬Â Research-Based Teaching Material Supplement Development as a Form of StudentsÃ¢â‚¬â„¢ Reproductive Health Care - Sa'adah, Laila Nur; Lisdiana, Lisdiana (Journal of Biology Education, 2020)
This research was aimed to analyze the advisability and the effectiveness of Ã¢â‚¬Å“RESENDSÃ¢â‚¬Â research-based teaching material supplement in improving the learning outcomes and fostering the studentsÃ¢â‚¬â„¢ reproductive health care. This research was conducted by using research and developmental methods (R&D) which refered to the modified Sugiyono (2013) steps. The result of this research showed that the advisability of Ã¢â‚¬Å“RESENDSÃ¢â‚¬Â research-based teaching material material was very decent (material validity 90.65%, media validity 99.2%, studentsÃ¢â‚¬â„¢ reponses 89%, teacher responses 96.7%). Ã¢â‚¬Å“RESENDSÃ¢â‚¬Â research-based teaching material supplement was effevtive in improving the studentsÃ¢â‚¬â„¢ learning outcomes and their care attitudes. It was proved by the percentage of studentsÃ¢â‚¬â„¢ classical completeness that had achieved the KKM Ã¢â€°Â¥ 72 was 87.9%. As many as 12% of the total students belonged to high criteria of caring attitude and 88% of the total students belonged to very high criteria. The conclusion of this research was Ã¢â‚¬Å“RESENDSÃ¢â‚¬Â research-based teaching material supplement was decent, valid, and effective in the biological study of reproductive system material.